Treatment of a case with hysterical hearing loss - Hegde MN; Jagadeesh RK (Journal of All India Institute of Speech and Hearing, 1970)
Miss N., a 18 year old girl reported to the  clinic on 4-7-69,  with a comp- laint of  hearing  difficulty.    She  said  she  was  experiencing  great  difficulty in hearing for the previous one  month.   The case came  to  the  clinic alone and on further questioning she was unable to specify the exact time of onset.    She felt that the problem could have  been  there even  earlier but  it was  probably negligible.   She also reported giddiness  from  the  age  of  8  years  which  was treated by several physicians but the case felt the treatment was ineffective.